2020
DOI: 10.1186/s12879-020-05013-7
|View full text |Cite
|
Sign up to set email alerts
|

The burden of laboratory-confirmed influenza infection in Lebanon between 2008 and 2016: a single tertiary care center experience

Abstract: Background: Influenza is a major cause of morbidity and mortality worldwide. Following the 2009 pandemic, there was widened interest in studying influenza burden in all regions. However, since data from the World Health Organization (WHO) Middle East and North Africa (MENA) region remain limited, we aimed to contribute to the understanding of influenza burden in Lebanon. Methods: A retrospective chart review extending over a period of 8 seasons from Jan 1st, 2008 till June 30th, 2016 at a tertiary care center … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
2
6
0
Order By: Relevance
“…The proportion of hospitalized severe influenza cases admitted to the ICU was 16.6% (17.8% for influenza A cases and 15.9% for influenza B cases), figures close to the 15.4% (23% for influenza A cases and 12.7% for influenza B cases) obtained by Stahl et al 39 in Germany in the same influenza season, and the 13.4% for influenza A cases and 17.8% for influenza B cases obtained by Assaf-Casals et al 24 in Lebanon during 2008–2016. Other authors studying severe patients have found higher figures 29 , but the differences in criteria for hospitalization might, at least in part, explain the differences.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The proportion of hospitalized severe influenza cases admitted to the ICU was 16.6% (17.8% for influenza A cases and 15.9% for influenza B cases), figures close to the 15.4% (23% for influenza A cases and 12.7% for influenza B cases) obtained by Stahl et al 39 in Germany in the same influenza season, and the 13.4% for influenza A cases and 17.8% for influenza B cases obtained by Assaf-Casals et al 24 in Lebanon during 2008–2016. Other authors studying severe patients have found higher figures 29 , but the differences in criteria for hospitalization might, at least in part, explain the differences.…”
Section: Discussionsupporting
confidence: 82%
“…The risk of death increased in the 65–74 years and ≥ 75 years age groups, coinciding with the findings of most studies reviewed 12 , 17 23 , although some authors found no differences in mortality according to age 24 .…”
Section: Discussionsupporting
confidence: 77%
“…In-person schooling in Lebanon was stopped on March 18, 2020 and remained remote for the duration of the period. This, along with other physical distancing measures and the general adherence of the public to masks and hand hygiene measures, that occurred aggressively and early in our setting, likely resulted in sudden drops of communicable disease, particularly influenza in spite of having the post-COVID-19 period coincide with the typical influenza season in Lebanon [ 21 ]. This is further supported by the association of a significant drop in overall ED visits after closure of in-person educational institutions including schools and universities.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first in Lebanon to explore vaccination rates and attitudes towards influenza vaccination among university students in three influenza seasons, using interventional awareness and descriptive surveys. In Lebanon, which has a burden of laboratory-confirmed influenza of about 14% and mortality of 3.8% [ 17 ], and with crises severely impacting the once top-tier healthcare system [ 18 ], an investigation of influenza vaccination status is important. In 2022, a meta-analysis of global influenza vaccination recommended more studies on this topic from the Eastern Mediterranean region [ 19 ], indicating that a profound understanding of influenza vaccination uptake and attitudes from our area is critical.…”
Section: Discussionmentioning
confidence: 99%